Surgical Management of Diaphragmatic Hernia in a Dog - Gaikwad, Shahir V; Khandekar, Gajendra S.; Tripathi, Santoshmani D; Rohi, Rajesh R; Rani, Monika (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Diaphragmatic hernia is a serious condition with a high mortality rate, characterized by the passage of abdominal organs into the thoracic cavity due to tear in the diaphragm. This condition, often resulting from trauma, leads to significant clinical symptoms (Ozer et al., 2007; Radlinsky and Fossum, 2013; Park and Lee, 2018; Yaygıngul et al., 2019; Zamirbekova et al., 2020). The diaphragm, which has a musculotendinous structure, is more robust at its center compared to its peripheral areas. Consequently, most abnormal openings occur where the diaphragm attaches to the ribs (Zamirbekova et al., 2020). In cats and dogs, diaphragmatic hernias result from congenital (5-10%) and traumatic (85%) causes, while 10-15% of cases have unknown origins (Radlinsky and Fossum, 2013; Park and Lee, 2018; Zamirbekova et al., 2020). A definitive diagnosis of diaphragmatic hernia requires radiography. Key radiographic indicators include the absence of the diaphragm line, a silhouetted appearance of the heart, lung displacement, and the presence of abdominal organs and gas within the chest cavity (Burns et al., 2013; Nikiphorou et al., 2016; Ozer et al., 2007). Surgical intervention is the sole treatment for diaphragmatic hernias (Park and Lee, 2018; Yaygıngul et al., 2019). This study details the diagnosis and successful surgical management of a traumatic diaphragmatic hernia in a 3-year old stray dog.